Mudanças de concepções de estudantes no ensino médio sobre a religião indígena Fulniô a partir do ciclo da experiência de George Kelly - Paz, Rosemary Pinheiro da (2018)
In the school space, indigenous culture and religion still face prejudice and discrimination, so we seek to contribute to a recognition of religious diversity and an attitude of respect for different beliefs, values, cultures and religion in the use of intercultural education. This work had the objective of analyzing the changes of conceptions of students in High School, in a Public School in the state of Pernambuco, on Indigenous Religion when using the methodology of the Kellyana Experience Cycle. The intervention was structured in five stages, through which the students had the opportunity to know, to reflect and to construct new information from their previous conceptions for new conceptions about the culture and religion of the Fulni-ô. The reference for the analysis of the data were the Curricular Parameters of Religious Education of the State of Pernambuco. We conclude that the use of the Kellyana Experience Cycle as a theoretical support to elaborate a didactic intervention met the expectations, indicating activities that made possible changes in students' conceptions regarding the indigenous religion of the Fulni-ô people. As well, it met the Learning Expectations of the Curricular Parameters of Religious Education. The pedagogical actions and organized from the previous knowledge of the students favor an effective action of him as a citizen in the community in which he is inserted.